Homeschooling: Between Croatian aspirations and Slovenian reality - Gita Mateja de Laat; Katarina Dadić; Rona Bušljeta Kardum (ÜNİVERSİTEPARK Limited, 2020)
In this study we describe a short history of homeschooling in Europe, with particular emphasis on Slovenia and Croatia. We describe the legal frameworks of both countries, with a focus mostly on Slovenia where homeschooling is legal, whilst in Croatia it is not legal. To find out how parents think about homeschooling and especially their thoughts about legislation on homeschooling, we conducted interviews with five Slovenian families who are already homeschooling their children and five Croatian families who aspire to do so, with the intention to gain clearer insight into the concrete reality of homeschooling in both countries. We address both the legislation and human experiences in order to examine to what extent the Slovenian example could form a basis for the creation of an authentic Croatian homeschooling model.